Paracetamol and ibuprofen removal from aqueous solutions by ozonation and photochemical processes - Trousil, Vojtěch; Palarčík, Jiří; Blažková, Zuzana; Kořínková, Jaroslava; Machalický, Oldřich; Cakl, Jiří (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The comparative experimental study has been performed of removal of pharmaceuticals such as paracetamol and ibuprofen from aqueous solution by ozonation and photochemical degradation in several types of reactors. Ozone, oxygen, and hydrogen peroxide were used as oxidizing agents. Heterogeneous photocatalysis was carried out in the presence of anatase type TiO2 catalyst. To determine the amount of radiation emitted by the UV lamps and transferred into the reactor, chemical feroxioxalate actinometric experiments were performed. The degree of the pollutant removal was monitored by HPLC, COD, BOD5, and TOC. An ecotoxic biological test of process products with Parachlorella kessleri was also evaluated. The results indicate that the removal of both pharmaceuticals is most effective by heterogeneous photocatalysis. In the UV processes, the degradation rate increased considerably when H2O2 was added. However, the addition of peroxide into the ozonation system improved the ozonation only slightly. All products of the processes tested showed improved biodegradability according to the BOD5/COD ratio and low toxicity to Parachlorella kessleri.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 159-175
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma